A Cybernetic Theory of Stress, Coping, and Well-Being in Organizations - Edwards, Jeffrey R. (Academy of Management Review, 1992)
Many major theories of organizational stress (OS) reflect basic principles of cybernetics, most notably the negative feedback loop. However, these principles are rarely examined in empirical OS research, which focuses predominantly on simple relationships embedded in OS theories. This problem may reflect an implicit rejection of cybernetic principles on conceptual grounds, the absence of specific propositions regarding these principles, methodological difficulties, or some combination of these factors. In any case, the result is a gap between theoretical and empirical OS research, which severely hinders the accumulation of knowledge in this area. This article is intended to narrow this gap by presenting an integrative cybernetic theory of stress, coping, and well-being in organizations, deriving propositions from this theory, and discussing methodological issues in testing this theory.